Multiple spatially distinct types of facultative heterochromatin on the human inactive X chromosome - Chadwick, Brian P. (National Academy of Sciences, 2004)
Heterochromatin is defined classically by condensation throughout the cell cycle, replication in late S phase and gene inactivity. Facultative heterochromatin is of particular interest, because its formation is developmentally regulated as a result of cellular differentiation. The most extensive example of facultative heterochromatin is the mammalian inactive X chromosome (Xi). A variety of histone variants and covalent histone modifications have been implicated in defining the organization of the Xi heterochromatic state, and the features of Xi heterochromatin have been widely interpreted as reflecting a redundant system of gene silencing. However, here we demonstrate that the human Xi is packaged into at least two nonoverlapping heterochromatin types, each characterized by specific Xi features: one defined by the presence of Xi-specific transcript RNA, the histone variant macroH2A, and histone H3 trimethylated at lysine 27 and the other defined by H3 trimethylated at lysine 9, heterochromatin protein 1, and histone H4 trimethylated at lysine 20. Furthermore, regions of the Xi packaged in different heterochromatin types are characterized by different patterns of replication in late S phase. The arrangement of facultative heterochromatin into spatially and temporally distinct domains has implications for both the establishment and maintenance of the Xi and adds a previously unsuspected degree of epigenetic complexity.